PERANAN SISTEM INFORMASI AKUNTANSI DALAM PROSEDUR PENGGAJIAN UNTUK MENINGKATKAN PENGENDALIAN INTERN PADA CV. MARGA SARANA ABADI SURABAYA - Pamungkas, Bagas Prayoga Septian; Hariyanto, Sugeng (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTThe purpose of this study was to determine how the application payroll accounting system on a CV . Marga Sarana Abadi Surabaya and to determine whether the payroll accounting system adopted by the company can assist management in internal control salary. This type of research is a kind of descriptive research that uses primary data such as interviews with the companies and the secondary as the organizational structure . Data was collected using observation , interview , and literature . Data analysis method used is descriptive method . This research was conducted in the office CV. Marga Sarana Abadi Surabaya is located in Jl . Kedung Asem PN - 01 Ruko Pondok Nirwana Surabaya and the time the study began in May 2016 until the completion of this thesis. The results of this study indicate that the accounting system applied to CV . Marga Sarana Abadi Surabaya to handle payroll and wages have been sufficient to help the company management in internal control salaries. This is good because the company employs a staff of various levels and the number of fairly and rewarded for their services in the form of salary , so the company must have an effective accounting system . Keywords : payroll , internal control , accounting information systems